Meningkatkan Ketahanan Mental pada Guru: Memaknai Stres Kerja Melalui Perspektif yang Positif - Nisrina Hanun Iftadi; Suwanda Priyadi; Taufik Imansyah; Muhammad Harisuddin Al-Munawwar; Icha Triya Amanda; Farah Hanifah Nuraini (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Teaching is considered as one of the jobs that is prone to high level of stress globally, this is related to the high workload and demands in dealing with students and parents. The lack of ability to manage job stress on teacher can bring harm effects such as worsening physical dan psychological health of teacher, worse learning experiences and quality outcomes, and reduce student achievement as well. The activities was aimed to help teachers to develop their ability in managing stress by providing knowledge about the positive sides of job stress and how to manage the stress effectively. The activities were carried out using lectures method and interactive discussion with the audiences. The measurement of the activities effectiveness was carried out using online questionnaire distributed through google form to 55 participants. The result of analysis showed that the activities was effective to increase the knowledge of the participants (p<0.001).